2010
DOI: 10.1007/s10530-009-9675-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure of the invasive alien red swamp crayfish

Abstract: High genetic diversity is thought to characterize successful invasive species, as the potential to adapt to new environments is enhanced and inbreeding is reduced. The red swamp crayfish, Procambarus clarkii, native to northeastern Mexico and southcentral USA was introduced to Nanjing, China from Japan in 1929. Little is known about the genetic diversity and population structure of this species in China. We examined the genetic diversity and population structure of six P. clarkii populations using nine polymor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
56
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 37 publications
(34 reference statements)
7
56
0
Order By: Relevance
“…High genetic diversity of introduced populations can be attributed to several factors: multiple introductions (Kolbe et al, 2004), a single introduction of a large number of individuals from different populations (Yue et al, 2010), and remote living locations and lower fishing pressure (Song et al, 2006). Yue et al (2010) have proved that the population in Nanjing, Jiangsu Province, may be the first invasive population of P. clarkii in China and that the translocation of P. clarkii from locations outside of China to Nanjing did not occur. The scale of introduction and fishing intensity in the HZ population of this species was relatively lower; which may cause high genetic diversity of introduced populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High genetic diversity of introduced populations can be attributed to several factors: multiple introductions (Kolbe et al, 2004), a single introduction of a large number of individuals from different populations (Yue et al, 2010), and remote living locations and lower fishing pressure (Song et al, 2006). Yue et al (2010) have proved that the population in Nanjing, Jiangsu Province, may be the first invasive population of P. clarkii in China and that the translocation of P. clarkii from locations outside of China to Nanjing did not occur. The scale of introduction and fishing intensity in the HZ population of this species was relatively lower; which may cause high genetic diversity of introduced populations.…”
Section: Discussionmentioning
confidence: 99%
“…Gene diversity has clearly decreased since crayfish were introduced to China in 1929 from Japan, which may have resulted from the presence of bottleneck and founder effects and nonrandom mating (Rozas et al, 1990). Yue et al (2010) have proved that the bottleneck effect is a crucial factor in gene diversity. Founder effects have been reported in a number of invasive species, including quagga mussel (Wilson et al, 1999), zebra mussel (Astanei et al, 2005), and Chinese mitten crab, which has invaded Europe (Herborg et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic analyses of Procambarus clarkii populations are being carried out around the world, using different molecular markers (Barbaresi et al, 2007;Yue et al, 2010;Li et al, 2012;Paulson and Martin, 2013) (Table 1). Genetic information can give helpful insights about connection between populations, and might help to infer the invasion history of exotic populations by identifying the location of origin, colonization events and dispersal routes and thus contribute to the understanding of invasion dynamics and to direct management efforts (Wilson et al, 1999;Kreiser et al, 2000;Lee, 2002;Reynolds and Souty-Grosset, 2012;Paulson and Martin, 2013).…”
Section: Geneticsmentioning
confidence: 99%
“…In China, Yue et al (2010) first studied 6 populations from East China and found evidences of a recent bottleneck and significant heterozygote deficit in all of them, suggesting founder effects and non-random mating; all populations also presented high genetic differentiation between each other. Later, Li et al (2012) used genetic information of 35 invasive populations from central and east China to investigate initial entry point(s), dispersal patterns, genetic diversity and genetic structure.…”
Section: Geneticsmentioning
confidence: 99%
“…However, the possibility exists that this reproduction behaviour mode is more widespread among cambarids, and may contribute to the success of this group when colonizing new habitats and territories. Asexual generations may also have contributed to observations of supposed P. clarkii clones by Yue et al (2008), and possibly to significant heterozygote deficiencies observed in Chinese populations of P. clarkii (Yue et al, 2010) as well as in some recent studies of existing invasive populations of O. limosus in the Czech Republic (Filipova et al, 2009), up to now explained by founder effects or assortative mating (Buřič et al, 2011(Buřič et al, , 2013.…”
Section: Parthenogenesismentioning
confidence: 95%